2015
DOI: 10.1523/jneurosci.2068-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Miro1 Regulates Activity-Driven Positioning of Mitochondria within Astrocytic Processes Apposed to Synapses to Regulate Intracellular Calcium Signaling

Abstract: It is fast emerging that maintaining mitochondrial function is important for regulating astrocyte function, although the specific mechanisms that govern astrocyte mitochondrial trafficking and positioning remain poorly understood. The mitochondrial Rho-GTPase 1 protein (Miro1) regulates mitochondrial trafficking and detachment from the microtubule transport network to control activity-dependent mitochondrial positioning in neurons. However, whether Miro proteins are important for regulating signaling-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
132
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 84 publications
3
132
1
Order By: Relevance
“…Here, the now stationary mitochondria help return Ca 2+ to baseline levels by directly taking up Ca 2+ and by providing ATP for the pumps that either extrude Ca 2+ or shunt Ca 2+ into the endoplasmic reticulum (Zündorf and Reiser, 2011). Mitochondrial Ca 2+ uptake further boosts ATP synthesis, which is necessary for high-frequency neurotransmitter release (Verstreken et al, 2005;Sheng, 2014;Rangaraju et al, 2014;Stephen et al, 2015).…”
Section: Mitochondrial Transport and Bioenergeticsmentioning
confidence: 99%
“…Here, the now stationary mitochondria help return Ca 2+ to baseline levels by directly taking up Ca 2+ and by providing ATP for the pumps that either extrude Ca 2+ or shunt Ca 2+ into the endoplasmic reticulum (Zündorf and Reiser, 2011). Mitochondrial Ca 2+ uptake further boosts ATP synthesis, which is necessary for high-frequency neurotransmitter release (Verstreken et al, 2005;Sheng, 2014;Rangaraju et al, 2014;Stephen et al, 2015).…”
Section: Mitochondrial Transport and Bioenergeticsmentioning
confidence: 99%
“…Beyond physical principles of cellular mechanics, mitochondrial distribution must be actively controlled to meet the needs of the cell. In that respect, mitochondrial enrichment has been described at subcellular areas with high ATP consumption, including axonal growth cones (Morris and Hollenbeck, 1993), presynaptic terminals, astrocytic processes near synapses (Stephen et al, 2015), viral assembly sites in ASFV (African swine fever virus)-infected cells (Rojo et al, 1998), and in cortical cytoskeleton of tumor cells (Desai et al, 2013) and oocytes (Guillemin et al, 2009; Van Blerkom and Davis, 2006). …”
Section: Descriptions Of Mitochondrial Morphologymentioning
confidence: 99%
“…For example, astrocyte mitochondria move slower than neuronal ones, perhaps pertaining to cell type-specific differences in the trafficking machinery (Fiacco and McCarthy, 2004). However astrocyte mitochondria are still capable of covering the same distances as neuronal mitochondria (Stephen et al, 2015). Hence, in addition to mitochondrial velocity, assessment of the distance covered by moving mitochondria may be of interest.…”
Section: Descriptions Of Mitochondrial Morphologymentioning
confidence: 99%
“…While GLT-1 (GLAST, glutamine synthetase, Na + /K + -ATPase, etc) have been localized to the fine processes of astrocytes (Chaudhry et al, 1995; Cholet et al, 2002; Norenberg and Martinez-Hernandez, 1979), there was a general belief that mitochondria were too large to fit into these fine processes (in many other cells mitochondria are 1 μm in diameter or larger). In fact, several studies have demonstrated the presence of mitochondria in fine astrocytic processes (Aoki et al, 1987; Derouiche et al, 2015; Fernandez et al, 1983; Genda et al, 2011; Jackson et al, 2014; Lovatt et al, 2007; Mathiisen et al, 2010; Motori et al, 2013; Mugnaini, 1964; Oberheim et al, 2009; Stephen et al, 2015; Xu et al, 2003 for review, see Stephen et al, 2014). In organotypic hippocampal slice cultures, mitochondria occupy 45% of the average astrocytic process and overlap with GLT-1 puncta occurs more often than would occur by chance (~70% of the time) (Genda et al, 2011).…”
Section: Coupling Of Glutamate Transport To Mitochondriamentioning
confidence: 99%
“…In organotypic cultures of rat hippocampus, astrocytes maintain their highly branched morphology (Benediktsson et al, 2005). Using this system and biolistically introduced fluorescent reporter proteins, we and others have recently demonstrated that between 15 and 30% of mitochondria are mobile in astrocytic processes (Jackson et al, 2014; Stephen et al, 2015). In some of our analyses, the percentage of mobile mitochondria was as low as 15%.…”
Section: Coupling Of Glutamate Transport To Mitochondriamentioning
confidence: 99%